Analisis Peran Swasta dan Pemerintah terhadap Kesempatan Kerja di Jawa Tengah Tahun 2019-2022 - Suci Ningtyas Handayani; Umayatu Suiroh Suharto (Diponegoro Journal of Economics, 2024)
This research was carried out to analyze the influence of Manufacture, Wage, and Government Expenditure on Employment in Central Java province in 2019 – 2023.  The analysis method in this research uses the Panel Data Method. Based on the result of the analysis it was concluded that the best analysis model was the Random Effect Model (REM). The results of the partial analysis are that manufacturing and government expenditure do not influence employment. Meanwhile, there is an influence of wages on employment.